Summary proceedings : annual meetings of the boards of governors - World Bank Group; World Bank.; International Finance Corporation; International Development Association; Multilateral Investment Guarantee Agency; International Centre for Settlement of Investment Disputes (Berlin (West) : World Bank, 1988)
These Summary Proceedings include statements, or portions of statements, relating to the work of the Fund presented by Governors during the meetings, resolutions adopted by the Board of Governors of the Fund over the past year, reports, recommendations and other documents relating to the Meetings.
Vols. for <1994-> published: Washington, D.C.
oif 06/03/15
Ref.
Keywords: Banks and banking, International; Banks and banking, International